Genetic diversity and antifungal resistance in Candida albicans from VVC cases in Indian women - Binaya Krushna Sahu; Utkalika Mallick; Rashmi Hegde; Jyotirmayee Turuk; Mahesh Chandra Sahu; Sujogya Kumar Panda (BMC Microbiology)
Abstract Background Vulvovaginal candidiasis (VVC) is a common fungal infection primarily caused by Candida albicans. It is associated with significant morbidity, especially in recurrent cases. Antifungal resistance, particularly to azole drugs, poses a growing challenge in treatment. Aim This study investigates the genetic diversity and antifungal resistance patterns of C. albicans isolated from VVC patients. Method A total of 170 vaginal swab samples were collected from Indian women attending the obstetrics and gynecology departments at IMS SUM Hospital and Kalinga Hospital, Odisha, India. C. albicans isolates were identified through microscopic analysis, growth on HiCrome™ Candida Differential Agar, germ tube formation tests, and the Vitek2 Compact system. Antifungal susceptibility was determined using the Kirby-Bauer disk diffusion method. Genetic diversity was assessed through Inter-Simple Sequence Repeat (ISSR) and Random Amplified Polymorphic DNA (RAPD) marker techniques. The data were analyzed using dendrograms, genetic similarity matrices, and Principal Component Analysis (PCA). Results Out of 170 vaginal swabs, 122 Candida isolates were identified, with 35 confirmed as C. albicans. Eighteen representative C. albicans isolates were analyzed for genetic diversity. Antifungal susceptibility tests revealed that Nystatin showed the highest sensitivity (60%), followed by miconazole (54.29%) and fluconazole (42.86%). In contrast, ketoconazole and voriconazole exhibited the highest resistance rates (60%). Itraconazole and clotrimazole also showed considerable resistance at 51.43% and 48.57%, respectively. Amphotericin B demonstrated moderate efficacy, with 20% sensitivity and a high intermediate response (45.71%). Genetic diversity analysis using ISSR and RAPD markers showed considerable polymorphism, indicating a heterogeneous C. albicans population. Strain S95 exhibited significant genetic divergence compared to other isolates, suggesting unique genetic characteristics. Both dendrograms and PCA identified distinct genetic clusters within the isolates. Conclusion The study demonstrates significant genetic variability among C. albicans isolates and widespread antifungal resistance, particularly to azole-based treatments. The results underscore the importance of regular monitoring of genetic diversity and resistance patterns in C. albicans to guide effective treatment strategies for VVC.